Aronia melanocarpa Fruit Bioactive Fraction Attenuates LPS-Induced Inflammatory Response in Human Bronchial Epithelial Cells - Bong-Keun Jang; Jin-Woo Lee; Hyun Choi; Sung-Vin Yim (MDPI AG, 2020)
To demonstrate the anti-inflammatory activity of Aronia melanocarpa fruit extract, human bronchial epithelial cells (BEAS-2B) were treated with lipopolysaccharide (LPS) and the effects of aronia bioactive fraction (ABF®), anthocyanin enriched extract from the fruit of A. melanocarpa, were evaluated. Following pretreatment with ABF® at 10-25 µg /mL, BEAS-2B cells were exposed to LPS and the expression of inflammatory mediators (tumor necrosis factor [TNF]-α, interleukin [IL]-6, IL-8, regulated upon activation, normal T cell expressed and presumably secreted [RANTES], IL-1β, cyclooxygenase-2 [COX-2], and inducible nitric oxide synthase [iNOS]) was analyzed. In LPS-stimulated BEAS-2B cells, ABF® pretreatment significantly decreased the mRNA expression of TNF-α, IL-6, IL-8, RANTES, IL-1β, and COX-2 at doses of 10 and 25 µg/mL. ABF® also attenuated the secretion of TNF- α, IL-6, IL-8, and RANTES protein, as demonstrated by enzyme linked immunosorbent assay. Western blot analyses revealed the decreased expression of COX-2 and iNOS following ABF® treatment. ROS production was decreased, and the cell cycle was arrested at the G0/G1 and S phases following ABF® pretreatment. Our results suggest that ABF® may have potential as a nutraceutical agent for the suppression of airway inflammation.